GAPLE SEBAGAI PROSES KOMUNIKASI DAKWAH DI RW. 02 CIPADUNG - Shilah Suci Anugerah; Abi Hasbi Ramdhan; Wawan Setiawan (Institut Nahdlatul Ulama Tasikmalaya, 2023)
Gaple activities are entertainment that is considered easy and cheap for the community to do. The culture inherent in society which is integrated with certain knowledge can create and give birth to superior seeds who will not only enjoy entertainment but will carry out critical thinking and understanding of that culture, both from religious, social and other scientific aspects. The aim of this research is to define communication through the gaple card game as an interaction process and the communication process as an aspect of social change. Ustadz Saepudin and Ustadz Yayat Hidayat Rahmat's communication in the interactive process of transmitting religious values ​​through the gaple game made them feel accepted. This research is a type of descriptive qualitative research, namely research that uses a case study approach method. This research focuses intensely on one topic, which is examined on a case-by-case basis. This research focuses intensely on one topic, which is examined on a case-by-case basis. Where this method allows researchers to remain intact and meaningful. The results of this research show that the Gaple game in RW 02 is not just a game but contains a philosophical meaning in the message of da'wah, namely, gaple as a process of forming social interactions in da'wah, there is an understanding of gaple cards which consist of 6 kinds of final cards in each game, which are inserted with values- Religious values ​​as a form of communicative activity which aims to unite religion in the person of each player or the process of understanding and internalizing religious values. The 6 (six) gaple cards have a da'wah philosophy, namely: First, balak one, is the philosophy that there is no god who must be worshiped except Allah, the Almighty. Second, balak dua contains the philosophy that in this world there are always pairs. Third, Balak Tiga, contains values ​​regarding the pillars of religion. Then in the process, da'wah forms social change leading to solving real problems, meaning that Islamic communication becomes one of the efforts or solutions to problems in the lives of the people in the socio-cultural, economic and political fields within the framework of modern society.